On-chip electro-optic multiplexing circuit using serial microring boxcar filters - Ali, J. (Elsevier B.V., 2018)
We propose a new variant of electro-optic multiplexing scheme using the boxcar filter arrangement. The circuits consist of multistage add-drop multiplexers that can offer external input-output connections. Input from a single light source can be fed into the system through the input port or through the free-space from light fidelity (LiFi) node. The light signal is fed into boxcar filters and the roll-off bands are obtained. The output of the circuits is formed at the drop, through and the whispering gallery mode (WGM) node of the circuit output. By using the electro-optic conversion in Si-Graphene-Au layer stack, time division (TDM), wavelength division (WDM), frequency division multiplexing (FDM) can be performed. The simulations have shown that a combination of 7 roll-off bands with the maximum spectral widths or bandwidths of ∼6.09 µm or ∼7.63 THz can be obtained.